Reply to Proffitt, Stefanucci, Banton, and Epstein - Hutchison, Jeffrey J.; Loomis, Jack M. (The Spanish Journal of Psychology, 2006)
In this reply, we acknowledge that methodological differences between the experiment of Proffitt et al. (2003) and ours might explain our failure to replicate their finding. However, we maintain that our results obtained with three different response measures point to a lack of robustness. In this reply, we acknowledge that methodological differences between the experiment of Proffitt et al. (2003) and ours might explain our failure to replicate their finding. However, we maintain that our results obtained with three different response measures point to a lack of robustness of their finding. In response to their criticism of using blind walking to measure perceived distance, we argue on theoretical grounds that blind walking, while involving post-perceptual processes, can nevertheless provide a measure of perceived distance, and then cite some of the evidence indicating that it does indeed provide such a measure.